Peran Guru dalam Membentuk Tanggung Jawab Siswa Kelas V Sekolah Dasar - Imam Suwardi Wibowo; Siti Maqfirotun (Jurnal Gentala Pendidikan Dasar, 2016)
The aim of this study to elucidate the role of teachers is shaping the student’s responsibility class V SD Negeri 111/1 Muara Bulian. This study uses approch qualitative descriptive. The data collection is clone by observation, and interview teachniques. The data analysis technique with data reduction, data presenstation conclusion and verikation the realiability of the results obtained by the triangulation teachninque in order to meet the criteria kreadibilitas realiance and objectivity. The role of teachers in shaping the student’s responsibility class V SD Negeri 111/1 Muara Bulian. Teachers have been instrumental in shaping the student’s responsibility. It can be seen from adherence to all indicators. Howerver there are two descriptors that al though already implemented teacher, they found some students who do not responsible like not doing homework or cheating during given training. The conclusion of this study is that teachers in shaping the student’s responsibility class V SD Negeri 111/1 Muara Bulian. Teachers use role as education and teachers as mentors.